Improving student competence through innovation of Islamic boarding school-based learning strategic - Alvida Dzattadini; Devina Amelia; Livia Anggina; M. Raihan Eka Putra (Curricula: Journal of Curriculum Development, 2025)
The implementation of the Kurikulum Merdeka with Daarut Tauhiid Boarding School Curriculum at SMK Daarut Tauhiid Boarding School has been going on for three years. This study aims to evaluate the effectiveness of implementing a curriculum that combines academic, vocational, and character aspects based on boarding school values to create graduates who are technically superior, highly moral, and competitive at the national and international levels. Using a qualitative approach, data was collected through observations, interviews, and document studies. The findings show that the Kurikulum Merdeka focuses on a competency-based learning approach that encourages student creativity and independence, while the Daarut Tauhiid Curriculum emphasizes the formation of good and strong character according to pesantren values. The use of technology such as the Learning Management System (LMS) facilitates efficient and interactive learning implementation. This curriculum integration allows students to excel technically and have a strong character. The combination of vocational education, pesantren values, and digital technology can produce nationally and internationally competitive graduates, as well as highly moral graduates.   Abstrak Implementasi Kurikulum Merdeka dengan Kurikulum Daarut Tauhiid khas pesantren di SMK Daarut Tauhiid Boarding School telah berlangsung selama tiga tahun. Tujuan penelitian ini untuk mengevaluasi efektivitas penerapan kurikulum yang mengkombinasikan aspek akademik, vokasi, dan karakter berbasis nilai-nilai pesantren, guna menciptakan lulusan yang unggul secara teknis, bermoral tinggi, dan kompetitif di tingkat nasional maupun internasional. Dengan pendekatan kualitatif, data dikumpulkan melalui observasi, wawancara, dan studi dokumen. Temuan menunjukkan bahwa Kurikulum Merdeka berfokus pada pendekatan pembelajaran berbasis kompetensi yang mendorong kreativitas dan kemandirian peserta didik, sementara Kurikulum Daarut Tauhiid menekankan pembentukan karakter baik dan kuat sesuai nilai-nilai pesantren. Penggunaan teknologi seperti Learning Management System (LMS) mempermudah pelaksanaan pembelajaran yang efisien dan interaktif. Integrasi kurikulum ini memungkinkan peserta didik unggul secara teknis dan memiliki karakter yang kuat. Kombinasi antara pendidikan vokasi, nilai-nilai pesantren, dan teknologi digital mampu menghasilkan lulusan yang kompetitif secara nasional dan internasional, serta bermoral tinggi. Kata Kunci: kompetensi peserta didik; kurikulum pesantren; pengembangan kurikulum; strategi pembelajaran